Analisis Pengaruh Pemasaran Digital dan Kualitas Produk Terhadap Keputusan Pembelian Pada PT Zhisheng Pacific Trading - Ummu Habibah, Resya; Rakhmat; Yesi, Reni (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2024)
This study aims to determine whether digital marketing and product quality have an influence on purchasing decisions on Mixue ice cream products at the Bekasi branch. This study uses a data collection method, namely field research using statementor questionnaire data. By using the sample method, namely the slovin method, which amounted to 133 respondents at consumers of Mixue ice cream products at the Bekasi branch. Results of the multiple regression coefficient analysis Y = 8.3690 + 0.1721 (X1) + 0.6142 (X2). Based on the calculation of the coefficient of determination analysis R2 is 0.7157, which means that the contribution of digital marketing and product quality can explain purchasing decisions by 71.57%. Based on the partial test results of digital marketing, it is obtained t count > t table of 2.708 > 1.978. Based on the partial test results of product quality, it is obtained t count > t table of 11.556 > 1.978. Based on the f hypothesis test is 167.218 > 3.07, then Ho is rejected and Ha is accepted, meaning that there is a significant influence between digital marketing (X1) and product quality (X2) on the purchasing decision variable (Y) at PT Zhisheng Pacific Trading.